PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KREATIVITAS SISWA SEKOLAH DASAR - KUSMIATI KUSMIATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research is motivated by the low creativity of science students in elementary schools. Education in the era of the industrial revolution 4.0 is expected for students to have high creative abilities to be able to solve problems in real life every day. To realize the achievement of these expectations, an innovative and creative learning model is needed, namely Project based Learning. This study aims to determine the effect of the project-based learning model on the creativity of elementary school students. This study uses a quantitative approach with the type of pre-experimental research using a one group pretest-posttest design. The research subjects were students of SD Negeri Kamal 1 Bangkalan, totaling 32 students. Data collection techniques using a questionnaire instrument. Judging from the average creativity of students before being given project based learning was 24.59 and after being given project based learning the average value was 34.81, meaning there was an increase of 11.22 so there was a difference before and after the application of the project based learning model. While the data hypothesis test using the paired sample t test technique obtained a sig (2-tailed) value of 0.000 which is smaller than 0.05, it can be concluded that there is an effect of the project based learning model on students' creativity. Project based learning is effective for increasing creativity skills in science lessons for fourth graders at the Kamal 1 Public Elementary School Bangkalan. ABSTRAKPenelitian ini dilatar belakangi rendahnya kreativitas siswa IPA disekolah dasar. Pendidikan di era revolusi industri 4.0 diharapkan peserta didik memiliki kemamampuan kreatifitas yang tinggi agar mampu memecahkan masalah-masalah dalam kehidupan nyata se hari-hari. Untuk mewujudkan ketercapaian harapan tersebut maka diperlukan model pembelajaran yang inovatif dan kreatif yaitu pembelajaran Project based Learning. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran project based learning terhadap kreativitas siswa sekolah dasar. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian pre eksperimen dengan menggunakan one group pretest-posttest design. Subyek penelitian siswa SD Negeri Kamal 1 Bangkalan yang berjumlah 32 siswa. Tehnik pengumpulan data menggunakan instrumen angket. Dilihat dari rata-rata kreativitas siswa sebelum diberi project based learning adalah 24,59 dan sesudah diberi project based learning rata nilainya 34.81 berarti ada kenaikan sebesar 11,22 jadi ada perbedaan sebelum dan sesudah penerapan model pembelajaran project based learning. Sedangkan Uji hipotesis data dengan menggunkan teknik paired sampel t test diperoleh nilai sig (2-tailed) 0,000 lebih kecil dari 0,05 maka dapat disimpulkan bahwa ada pengaruh model pembelajaran project based learning terhadap kreativitas siswa. Pembelajaran project based learning efektif untuk meningkatkan kemampuan kreativitas dalam pelajaran IPA siswa kelas IV sekolah dasar negeri kamal 1 Bangkalan.